The Effect of Hot Pressing on the Mechanical Properties of Metal Composites (AI/Sic) Result from Metallurgical Processes with Heating Temperature Variations in Bushing Making - ., Mangambari; Arma, Lukmanul Hakim; Syahid, Muhammad (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2023)
The manufacture of Al/SiC alloy matrix composites has been widely carried out by researchers through powder metallurgy techniques. Bushings are slit cylindrical type bearings that serve to support the shaft. Bushings can be made by powder metallurgy, to get the perfect compaction process, compaction can be done by high temperature or Hot Pressing. A hot press will make the powder softer/plastic, making it easier during the perfect compaction process. For this reason, heating must be controlled in order to obtain a homogeneous product. Al/SiC metal matrix composites are alloyed materials of different types of materials, as matrices in this case are aluminum and as reinforcement are SiC particles (ceramics) made by powder metallurgy techniques. In this study, the Al/SiC composite composed of 70% Al - 30% SiC and Hot Pressing temperature variations of 100, 150 and 200°C with a pressure of 5000 kg and a holding time of 10 minutes. In the sintering process, the temperature used is 450, 500 and 550°C with a holding time of 2 hours. The results of this study show, in hardness testing it is known that the value of bushing hardness increases as the temperature of Hot Pressing increases.